Confidential memorandum : conversation between Julius Deutsch and the editor of 'Populaire'
1937-08 016b-0059-002 CONFIDENTIAL MEMORANDUM 12.8.37. The views expressed hereunder are also those of the Valencia Government. The most important thing for the Government now is the swift withdrawal of volunteers, There are about 7,000 on the Government side and between 30,000 and 40,000 on the rebel side. If there were withdrawal of all volunteers and not merely proportionate withdrawal - one for one - it would be to the advantage of the Government. The question of withdrawing Franco's coloured troops is unimportant. The good fighting Moroccans were all killed in the early engagements. The North Africans now in Franco's array are just "cannon-fodder' and the Government has at least equivalent supplies of that kind. What is important is to secure the withdrawal of the Italian and German technicians - airmen, artillerymen, anti-tank experts and so on. If they were withdrawn, a big advantage would rest with the Government. The Government would be prepared to accept even a procedure that might be suggested by Great Britain of sending investigating commissions to Spain before the organisation of withdrawal was worked out. It is firmly believed that Franco would accept the withdrawal of volunteers in exchange for the rights of a belligerant, because his need of credits is so great that he would be prepared to make almost any sacrifices to get them - and he cannot get them until he is accorded belligerent rights. It is believed that if Great Britain in agreement with France took a really strong stand on this question Franco would accept. It is known that several countries would support such a lead fully, including Norway and Belgium 292/946/16b/65(ii)